Histopathological spectrum of intrathoracic lesions (Journal of Pathology of Nepal, 2022)
Background: Any suspicious lesion in the chest on radiology needs further workup. Conventional bronchoscopy or CT-guided fine needle aspiration may help in evaluating these suspicious lesions.Materials and methods: The study was carried out in the pathology department of a tertiary care hospital over a period of 2 years. Clinical details were taken from the records. Samples were processed by routine histological techniques and stained with hematoxylin and eosin.Results: A total of 100 cases were analyzed. Most of the lesions were in the lungs (97%), 2% in the pleura, and 1% in the mediastinum. The most common malignancy was squamous cell carcinoma (29%) followed by adenocarcinoma (24%) and small cell lung carcinoma (9%). The most common benign lesions were tuberculosis (4%), organizing pneumonia (3%), and bronchiectasis (2%).Conclusions: The present study concludes that histopathological examination gives maximum accuracy in diagnosing a patient with suspicious intrathoracic lesions so that the patient can be started on treatment immediately.